Self-supported bifunctional water-splitting catalysts, preparation and use thereof

CN116180119BActive Publication Date: 2026-10-30CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310151110.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-22
Publication Date
2026-10-30
Estimated Expiration
2043-02-22

AI Technical Summary

Technical Problem

此外,大多数HER催化剂只能在酸性电解液中发挥更好的催化效果,而OER催化剂往往在碱性电解液中具备更好的催化性能

Benefits of technology

[0040](1)本发明提供了一种全新的催化剂,其以多孔金属为骨架,且在骨架上原位负载有活性成分,所述的活性成分包含氧缺陷LDH和尖晶石协同复合物相。本发明所述的材料,基于所述的复合物相的活性成分的联合控制,能够实现协同,能够赋予材料优异的HER和OER双功能。例如,本发明所述的催化剂,其可以在高电流(大于或等于1000mA cm-2)下还能够兼顾优异的HER以及OER性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116180119B_ABST
    Figure CN116180119B_ABST
Patent Text Reader

Abstract

The application belongs to the field of electrocatalysis, and particularly relates to a self-supporting bifunctional water electrolysis catalyst, which comprises a foam metal M and active ingredients loaded in situ on the skeleton of the foam metal M; the active ingredients comprise metal M-metal N hydrotalcite nanosheets with oxygen vacancy defects and spinel oxides of metals M and N loaded on the nanosheets; M and N are transition metals; the application also comprises preparation of the material and application of the material in HER and OER dual catalysis; the material has excellent HER and OER dual functional catalytic effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalysis, specifically relating to catalysts for water electrolysis. Background Technology

[0002] Against the backdrop of the energy crisis and environmental degradation, the task of finding sustainable clean energy to replace fossil fuels is urgent. Hydrogen, as a high-energy-density, green, renewable, and clean energy carrier, holds promise as an ideal clean energy source for future society. Compared to traditional hydrogen production methods such as methanol reforming and coal gasification, water electrolysis offers significant advantages, including simpler processes, less environmental pollution, and higher hydrogen purity. However, due to the large overpotential present during water electrolysis, the energy conversion efficiency of this process remains less than ideal. Therefore, a highly efficient water electrolysis catalyst is crucial to overcoming the bottlenecks in the development of water electrolysis for hydrogen production.

[0003] Water electrolysis involves the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Currently, the most widely used catalysts for HER and OER are Pt-based and Ru / Ir-based oxide catalysts, respectively. The limited reserves and high prices of these precious metal catalysts hinder the development of large-scale water electrolysis for hydrogen production. Therefore, abundant and inexpensive transition metal catalysts have become a better alternative to precious metal catalysts. Furthermore, most HER catalysts exhibit better catalytic performance only in acidic electrolytes, while OER catalysts often demonstrate better catalytic performance in alkaline electrolytes. This undoubtedly presents significant challenges to the design of the electrolyzer and the selection of the ion exchange membrane.

[0004] Therefore, developing bifunctional transition metal catalysts that simultaneously possess HER and OER activities is a very promising approach. Summary of the Invention

[0005] To address the aforementioned issues, this invention provides a self-supporting bifunctional water electrolysis catalyst, aiming to provide a catalyst that combines both HER and OER functions.

[0006] The second objective of this invention is to provide a method for preparing the aforementioned self-supporting bifunctional water electrolysis catalyst, aiming to obtain a catalyst that combines both HER and OER functions.

[0007] A third objective of this invention is to provide the application of the self-supporting bifunctional water electrolysis catalyst in water electrolysis, as well as electrodes and batteries comprising the bicatalyst.

[0008] The catalytic requirements for OER and HER are different, and existing catalysts struggle to achieve bifunctionality for both OER and HER. Even the few catalysts that claim to be bifunctional do not exhibit ideal bifunctional catalytic capabilities. To address this problem, this invention provides the following solution:

[0009] A self-supporting bifunctional water electrolysis catalyst, comprising a foam metal M and an active component supported in situ on its framework;

[0010] The active ingredients include hydrotalcite nanosheets with oxygen vacancy defects of metal M-metal N, and spinel oxides loaded with metal M and N on the nanosheets;

[0011] M and N are transition metals.

[0012] This invention provides a material with a novel structure and phase, which achieves synergistic effects by combining a porous framework in-situ supported structure with oxygen vacancy defects in the hydrotalcite nanosheets of metal M-metal N, and the phase composition of spinel oxides of metal M and N. This allows it to exhibit excellent dual-function HER and OER catalysis. For example, the material described in this invention can exhibit excellent dual-function HER and OER catalytic activity even at high currents.

[0013] In this invention, metals M and N are each at least one of iron, cobalt, nickel, and copper; and metals M and N are selected from different elements.

[0014] Preferably, the metal M is iron and the N is cobalt; or, the metal M is cobalt and the N is iron.

[0015] Preferably, the spinel oxide is at least one of cobalt ferrite and iron cobaltate.

[0016] Preferably, the metal M is iron and the N is cobalt; an MN alloy phase exists at the interface between the metal M and the active component, as well as on the hydrotalcite nanosheets. Studies have found that this preferred alloy phase composite can further synergistically improve the OER and HER properties of the material.

[0017] The present invention also provides a method for preparing the self-supporting bifunctional water electrolysis catalyst, wherein a raw material solution containing foam metal M, metal N source and hydrolysant is reacted under normal pressure to obtain the self-supporting bifunctional water electrolysis catalyst.

[0018] The initial raw material solution contains a molar concentration of metallic nitrogen (N) ≤ 2M; the hydrolyzing agent is at least one of thiourea and thiosulfate.

[0019] The difficulty in preparing the catalyst described in this invention lies in constructing an in-situ composite morphology and simultaneously building the composite phase and structure of the oxygen-deficient hydrotalcite and spinel oxide. To address this challenge, this invention innovatively involves reacting foam metal M, a metal N source, and a hydrolysate at atmospheric pressure. By combining the control of the type of hydrolysate, the concentration of the metal N source, and the temperature of the atmospheric pressure reaction during the reaction stages, synergistic effects can be achieved. This allows for the one-step construction of the desired synergistic composite phase and structure, contributing to the synergistic improvement of the prepared material's HER and OER bifunctional properties.

[0020] In this invention, the thickness of the foamed metal M is 1.0-2.0 mm, and the porosity is 20-99%, more preferably 70-99%.

[0021] Preferably, the foamed metal M is pretreated before the reaction; the pretreatment steps include acid washing and water washing.

[0022] Preferably, the concentration of the pickling acid solution is 0.1–3 M, and more preferably 0.5–1.5 M.

[0023] In this invention, the metal N source is a water-soluble salt of metal N, preferably at least one selected from chloride, sulfate, nitrate, and organic acid salt. Preferably, the molar concentration of metal N in the initial raw material solution is 0.1–1.5 M, more preferably 0.1–0.5 M.

[0024] Preferably, the thiosulfate in the hydrolysing agent is a water-soluble salt, such as sodium thiosulfate.

[0025] Preferably, the concentration of the hydrolysant in the initial raw material solution is ≤2M, and more preferably 1-2M;

[0026] Preferably, the molar ratio of metal N source to hydrolysant is 1:0.1 to 15, and more preferably 1:1 to 5.

[0027] Preferably, the atmospheric pressure reaction is carried out in an open reaction vessel;

[0028] Preferably, the temperature of the atmospheric pressure reaction stage is 75–90°C, and more preferably 80–90°C.

[0029] Preferably, the reaction time under normal pressure is 1 to 72 hours; considering the preparation efficiency, it is further preferred to be 2 to 5 hours.

[0030] Preferably, the reaction is carried out under normal pressure, followed by washing with water and drying to obtain the self-supporting bifunctional water electrolysis catalyst.

[0031] This invention discloses a method for preparing a self-supporting bifunctional water electrolysis catalyst, comprising the following steps:

[0032] Step (1): Prepare a solution by dissolving metal salt N: hydrolysant = 1:(1~15) in water at a molar ratio to obtain solution I;

[0033] Step (2): Cut the foam metal M into small pieces, soak them in 1 mol / L acid solution D for 60-90 seconds, and then sonicate them in pure water for 10-15 minutes.

[0034] Step (3): Immerse the foam metal M treated in step (2) in solution I, react in a water bath at atmospheric pressure and 60-90℃ for 1-72 hours, rinse with pure water and perform electrocatalytic testing.

[0035] The present invention also provides an application of the self-supporting bifunctional water electrolysis catalyst described above, using it as a catalyst for HER and / or OER for catalytic electrolysis of aqueous solutions;

[0036] Preferably, the aqueous solution is an alkaline aqueous solution; the solute is preferably 0.1 to 3 M.

[0037] The present invention also provides a device, such as a battery, comprising the self-supporting bifunctional water electrolysis catalyst described herein and the electrode.

[0038] In this invention, the electrodes and equipment required for preparing the self-supporting bifunctional water electrolysis catalyst described in this invention can be prepared using existing methods.

[0039] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0040] (1) This invention provides a novel catalyst with a porous metal framework on which active components are in-situ supported. These active components comprise an oxygen-deficient LDH and a spinel synergistic complex phase. The material of this invention, based on the combined control of the active components in the complex phase, can achieve synergy and endow the material with excellent HER and OER dual functionality. For example, the catalyst of this invention can operate at high currents (greater than or equal to 1000 mA cm⁻¹). -2 It can also maintain excellent HER and OER performance.

[0041] (2) In view of the problem that it is difficult to impart the special complex phase and structure in one step in the preparation of the catalyst described in this invention, this invention innovatively carries out the reaction of foam metal and metal source under normal pressure with the assistance of hydrolysate, and based on the joint control of reaction temperature and metal N concentration, it can achieve synergy, and can construct the material with the special complex phase and structure in one step, and improve the excellent HER and OER performance of the prepared material.

[0042] (3) The technical solution of the present invention has a simple process and mild reaction conditions. The catalyst is grown directly in situ on the foam metal substrate without the need to add binders. The catalyst material is tightly bonded to the conductive substrate, which can meet the catalytic performance required for the high current density in the actual alkaline water electrolysis industrial application. Attached Figure Description

[0043] Figure 1 This is the X-ray diffraction (XRD) pattern of Embodiment 1 of the present invention;

[0044] Figure 2 This is a scanning electron microscope (SEM) image of Embodiment 1 of the present invention;

[0045] Figure 3 The LSV curves of the hydrogen evolution reaction of the material in Example 1 of the present invention and the materials in Comparative Examples 1, 2, and 3 are shown.

[0046] Figure 4 This is the oxygen evolution reaction LSV curve of the material in Example 1 of the present invention;

[0047] Figure 5 This is the LSV curve of the hydrogen evolution reaction of the material in Example 2 of the present invention;

[0048] Figure 6 This is the oxygen evolution reaction LSV curve of the material in Example 2 of the present invention.

[0049] Figure 7 LSV curves of hydrogen evolution reaction of the material in Example 3 and the material in Comparative Example 4.

[0050] Figure 8 LSV curves of hydrogen evolution reaction of the material in Example 4 and the material in Comparative Example 5. Detailed Implementation

[0051] The present invention will be further described below with reference to specific implementation examples. The following embodiments do not limit the scope of the present invention; any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

[0052] Example 1

[0053] Step (1): Cobalt nitrate (metal source N) is used as the metal salt and thiourea is used as the hydrolysis agent. Prepare a 50 mL mixed solution with the concentration of cobalt nitrate being 1.2 mol / L and the concentration of thiourea being 1.2 mol / L.

[0054] Step (2): The foam metal is made of foam iron (foam metal M, porosity 95%~98%). The foam iron is cut into small pieces of 2cm*3cm, soaked in 1mol / L hydrochloric acid solution for 90s, and then placed in pure water and sonicated for 15min.

[0055] Step (3): Immerse the foamed iron obtained in step (2) into the solution obtained in step (1), and react in an open reaction device at 80°C and normal pressure for 3 hours, then rinse it clean with pure water.

[0056] The HER and OER performance of the catalyst were tested in a three-electrode system at room temperature (test current 1000 mA cm⁻¹). -2 The electrolyte was a 1 mol / L KOH solution, and the resulting self-supporting electrode was used as the working electrode, with a counter electrode area of ​​1 cm². 2 The platinum sheet electrode is used, and the reference electrode is an Hg / HgO electrode. The LSV curve is corrected by iR to eliminate the influence of solution internal resistance.

[0057] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the material in Example 1, illustrating that the main substances on the surface of the self-supporting material are Co-Fe LDH, CoFe2O4, and CoFe alloy. Figure 2 The image shown is a scanning electron microscope (SEM) image of the material in Example 1, illustrating that the nanosheet-like catalytic material is uniformly grown on the foamed iron.

[0058] Comparative Example 1

[0059] Compared with Example 1, the only difference is that no hydrolysate was added in step (1), while the other operations and parameters are the same as in Example 1.

[0060] Comparative Example 2

[0061] Compared with Example 1, the only difference is that in step (1), the hydrolysant is replaced with an equimolar amount of thioacetamide.

[0062] Comparative Example 3

[0063] Compared with Example 1, the only difference is that in step (1), the hydrolysant is replaced with an equimolar amount of sodium sulfide.

[0064] Figure 3 The LSV curves of the hydrogen evolution reaction of the material in Example 1 and the materials in Comparative Examples 1, 2, and 3 illustrate that the material in Example 1 has excellent HER performance. Figure 4 The figure shows the oxygen evolution reaction (LOR) curve of the material in Example 1, illustrating that the material in Example 1 possesses excellent OER performance.

[0065] Example 2

[0066] Compared with Example 1, the only difference is that in step (1), the hydrolysant is replaced with an equimolar amount of sodium thiosulfate.

[0067] The HER and OER performance were tested using the method described in Example 1, and the results are as follows: Figure 5The LSV curve of the hydrogen evolution reaction of the material in Example 2 of this invention illustrates that the material in Example 2 has excellent HER performance. Figure 6 The LSV curve of the oxygen evolution reaction of the material in Example 2 of this invention illustrates that the material in Example 2 has excellent OER performance.

[0068] Example 3

[0069] The only difference from Example 1 is that the concentration of cobalt nitrate (metallic N) is 0.1 mol / L.

[0070] Comparative Example 4

[0071] The only difference from Example 1 is that the concentration of cobalt nitrate (metallic N) is 4 mol / L.

[0072] The HER performance was tested using the method described in Example 1, and the results are as follows: Figure 7 The LSV curves of the hydrogen evolution reaction in Example 3 and Comparative Example 3 illustrate that a catalyst with excellent catalytic performance can only be prepared within the preferred cobalt nitrate concentration range.

[0073] Example 4

[0074] The only difference from Example 1 is that the reaction temperature in step 3 is 90°C.

[0075] Comparative Example 5

[0076] The only difference from Example 1 is that the reaction temperature is 120°C (in a closed container).

[0077] The HER performance was tested using the method described in Example 1, and the results are as follows: Figure 8 The LSV curves of the hydrogen evolution reaction in Example 4 and Comparative Example 5 illustrate that catalysts with good catalytic performance can only be prepared within the preferred temperature range.

[0078] Example 5

[0079] The only difference from Example 1 is that the metal salt used is nickel nitrate (metal N), and the foam metal used is copper foam (metal M).

[0080] The HER and OER performance were tested using the method described in Example 1, and the result was 1000 mA / cm. -2 At the current density, the overpotential of HER is 350mV, and the overpotential of OER is 420mV.

[0081] Example 6

[0082] The difference from Example 1 is that the metal salt used is ferric nitrate (metal N), and the foam metal used is cobalt foam (metal M).

[0083] The HER and OER performance were tested using the method described in Example 1, and the result was 1000 mA / cm. -2 At the current density, the overpotential of HER is 360mV, and the overpotential of OER is 400mV.

Claims

1. A self-supporting bifunctional water electrolysis catalyst, characterized in that, This includes foamed metal M and active ingredients in situ loaded on its framework; The active ingredients include hydrotalcite nanosheets with oxygen vacancy defects of metal M-metal N, and spinel oxides of metal M and N supported on the nanosheets; M and N are transition metals; each of the metals M and N is at least one of iron, cobalt, nickel, and copper; and M and N are selected from different elements. The preparation method of the self-supporting bifunctional water electrolysis catalyst is as follows: a raw material solution containing foam metal M, metal N source and hydrolysant is reacted under normal pressure to obtain the self-supporting bifunctional water electrolysis catalyst. Wherein, the molar concentration of metallic N element in the initial raw material solution is ≤2M; the hydrolyzing agent is at least one of thiourea and thiosulfate; The temperature during the atmospheric pressure reaction stage is 60~90℃.

2. The self-supporting bifunctional water electrolysis catalyst as described in claim 1, characterized in that, The metal M is iron and the N is cobalt; or, the metal M is cobalt and the N is iron.

3. The self-supporting bifunctional water electrolysis catalyst as described in claim 2, characterized in that, The spinel oxide is at least one of cobalt ferrite and iron cobaltate.

4. The self-supporting bifunctional water electrolysis catalyst as described in claim 1, characterized in that, An MN alloy phase exists at the interface between metal M and the active component, as well as on the hydrotalcite nanosheets.

5. A method for preparing a self-supporting bifunctional water electrolysis catalyst according to any one of claims 1 to 4, characterized in that, The self-supporting bifunctional water electrolysis catalyst is prepared by reacting a raw material solution containing foam metal M, metal N source and hydrolysant under normal pressure. Wherein, the molar concentration of metallic N element in the initial raw material solution is ≤2M; the hydrolyzing agent is at least one of thiourea and thiosulfate; The temperature during the atmospheric pressure reaction stage is 60~90℃.

6. The preparation method of the self-supporting bifunctional water electrolysis catalyst as described in claim 5, characterized in that, The foamed metal M has a thickness of 1.0~2.0 mm and a porosity of 20~99%.

7. The preparation method of the self-supporting bifunctional water electrolysis catalyst as described in claim 6, characterized in that, Before the reaction, the foam metal M is pretreated. The pretreatment steps include pickling and washing; The concentration of the pickling acid solution is 0.1~3M.

8. The preparation method of the self-supporting bifunctional water electrolysis catalyst as described in claim 5, characterized in that, The source of metallic N is a water-soluble salt of metallic N.

9. The method for preparing the self-supporting bifunctional water electrolysis catalyst as described in claim 8, characterized in that, The metal N source is at least one of chloride, sulfate, nitrate, or organic acid salt.

10. The method for preparing the self-supporting bifunctional water electrolysis catalyst as described in claim 5, characterized in that, The initial raw material solution contains a molar concentration of metallic nitrogen (N) of 0.1–1.5 M.

11. The method for preparing the self-supporting bifunctional water electrolysis catalyst as described in claim 5, characterized in that, In the hydrolysing agent, the thiosulfate is a water-soluble salt; The concentration of the hydrolysant in the initial raw material solution is ≤2M; The molar ratio of metal N source to hydrolysant is 1:0.1~15.

12. The method for preparing the self-supporting bifunctional water electrolysis catalyst as described in claim 11, characterized in that, The concentration of the hydrolysant in the initial raw material solution is 1~2M; The molar ratio of metal N source to hydrolysant is 1:1~5.

13. The method for preparing the self-supporting bifunctional water electrolysis catalyst as described in claim 5, characterized in that, The reaction at atmospheric pressure is carried out in an open reaction vessel.

14. The method for preparing the self-supporting bifunctional water electrolysis catalyst as described in claim 13, characterized in that, The reaction time at normal pressure is 1~72 h; After reaction at atmospheric pressure, the mixture is washed with water and dried to obtain the self-supporting bifunctional water electrolysis catalyst.

15. The application of a self-supporting bifunctional water electrolysis catalyst according to any one of claims 1 to 4 or a self-supporting bifunctional water electrolysis catalyst prepared by the preparation method according to any one of claims 5 to 14, characterized in that, It is used as a catalyst for HER and / or OER in the catalytic electrolysis of aqueous solutions.

16. The application as described in claim 15, characterized in that, The aqueous solution is an alkaline aqueous solution with a solute concentration of 0.1~3M.

17. An electrode, characterized in that, The catalyst comprises the self-supporting bifunctional water electrolysis catalyst according to any one of claims 1 to 4 or the self-supporting bifunctional water electrolysis catalyst prepared by the preparation method according to any one of claims 5 to 14.

18. A battery, characterized in that, It includes the electrode as described in claim 17.